ELECTROSYNTHESIS AND PHOTORESPONSE OF THALLIUM CONTAINING CADMIUM SELENIDE FILMS - Md. Rashid Tanveer (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2008)
Thallium containing cadmium selenide deposited films of different compositions were synthesized on the titanium substrate by electrochemical codeposition technique. In order to study the effect of the inclusion of thallium on the properties of CdSe, these films were characterized for their optical properties, corrosion behaviour and capacitance studies. The optical properties revealed the presence of direct band gaps with energies in the range of 1.76 – 1.18eV depending upon the concentration of electroplating solution. The corrosion rate decreases sharply with increase in the concentration of TlNO3 in the electroplating solution up to certain limit and shows formation of more and more uniform and stable thin films using electroplating solution containing TlNO3 notexceeding 5 x 10-3 M concentration. The capacitance studies show that both the flat band potential and charge carrier density is seen to increase sharply with inclusion of thallium in the electroplating solution. The positive values of Efband photoactivity found in all cases and current voltage behavior in dark and under illumination show that the thin films are endowed with p- type of semiconductivity.